Examination of Nutrition Knowledge Levels of Individuals Who Received Sports Training: Life Sciences-Nutritional Science - Ceylan, Levent; Ezgi Akkaya Boyraz, Defne; Çaldiran, Sadettin; Ceylan, Tülay; Küçük, Hamza (International Journal of Life Science and Pharma Research, 2022)
The aim of this research is to determine whether the nutrition lessons taken affect the students, to what extent the students adapt the learned nutrition information to their lives, whether there is a relationship between the sports branch and nutrition information, whether there is a relationship between body mass index grouping and nutrition information. A total of 202 people, 125 (61.9%) men and 77 (38.1%) women, aged 23.21±3.31 years, participated in the study. In the first part of the data collection tool prepared in the research, the personal information of the participants was asked. In the second part, "Basic Nutrition Information" scale, in the third part "Food Preference" scale was asked. The factual questionnaire containing personal information consists of 16 questions in total. Multiple choice and open-ended questions were included in the questionnaire in which personal information was asked. The height and body weights of the participants were submitted by themselves. Body mass indexes (BMI) were calculated with the given body weight and height information ((BMI) = Body Weight (kg.) / Height squared (m2.)). The collected data were analyzed using the SPSS 22 package program. The homogeneity of the data was performed using the Scheffe and Hochberg GT2 test and the Post-Hoc multiple comparison test. Pearson Correlation test was used to determine the relationship between the nutritional knowledge levels of the individuals participating in the study and their age groups, since the data showed a normal distribution. The BMI and YETBID total scores of graduates and students were compared, a significant difference was found between graduates and students (p<0.05). A significant difference in the YETBI D total score was found to be in favor of graduates. BMI was found to be higher in graduates compared to students. No significant difference was found when BT total scores were compared (p>0.05). When the total scores of the participants were evaluated according to the status of taking courses, a significant difference was found in favor of those who took courses in both YETBID and BT. As a result; Nutrition education on proper nutrition (i.e. carbohydrates, protein and fluid) should be the main focus and priority, both in order to have an impact on public health, and to increase the performance of those who do sports and to aid recovery.